The last flight of Petr Ginz [videorecording (DVD)] - Dickson, Sandy; Roberts, Churchill Lee, 1940-; Pressburger, Chava, 1930-; Shendar, Yehudit (First Run Features, 2013)
By 14 he had written five novels and penned a diary about the Nazi occupation of Prague. By 16 he had produced more than 170 drawings and paintings, edited an underground magazine in the Theresienstadt Ghetto, written numerous short stories and had walked to the gas chamber at Auschwitz. But this is a story of celebration as well as tragedy, a testament to how a boy's wonder and creative expression represent the best of what makes us human.